Karyotype and genome size analyses for two spiders of the lycosidae family - Zhang, Yuxuan; Zhang, Mengying; Leng, Liang; Wu, Ya; Yang, Hanting; Wang, Liangting; Liu, Baimei; Yang, Shuai; Yang, Zizhong; Chen, Shilin; Song, Chi (Frontiers in Genetics, 2025)
BackgroundKaryotype and genome size are critical genetic characteristics with significant value for cytogenetics, taxonomy, phylogenetics, evolution, and molecular biology. The Lycosidae family, known for its diverse spiders with varying ecological habits and behavioral traits, has seen limited exploration of its karyotype and genome size.MethodsWe utilized an improved tissue drop technique to prepare chromosome slides and compare the features of male and female karyotypes for two wolf spiders with different habits of Lycosidae. Furthermore, we predicted their genome sizes using flow cytometry (FCM) and K-mer analysis.ResultsThe karyotypes of female and male Hippasa lycosina were 2n♀ = 26 = 14 m + 12 sm and 2n♂ = 24 = 10 m + 14 sm, respectively, and were composed of metacentric (m) and submetacentric (sm) chromosomes. In contrast, the karyotypes of Lycosa grahami consisted of telocentric (t) and subtelocentric (st) chromosomes (2n♀ = 20 = 20th and 2n♂ = 18 = 12th + 6t, for females and males). The sex chromosomes were both X1X2O. The estimated sizes of the H. lycosina and L. grahami genomes were 1966.54–2099.89 Mb and 3692.81–4012.56 Mb, respectively. Flow cytometry yielded slightly smaller estimates for genome size compared to k-mer analysis. K-mer analysis revealed a genome heterozygosity of 0.42% for H. lycosina and 0.80% for L. grahami, along with duplication ratios of 21.39% and 54.91%, respectively.ConclusionThis study describes the first analysis of the genome sizes and karyotypes of two spiders from the Lycosidae that exhibit differential habits and provides essential data for future phylogenetic, cytogenetic, and genomic studies.